Italian biodistricts and French territorial food projects: how science-policy-experience interplays shape the framings of transitions towards sustainable territorial food systems - Lamine, Claire; Pugliese, Patrizia; Barataud, Fabienne; Berti, Giaime; Rossi, Adanella (Frontiers in Sustainable Food Systems, 2023)
The territorial scale is increasingly recognised as a relevant scale for analysing, conceiving and supporting the ecological transitions of agri-food systems. France and Italy have both been pioneer countries for the valorisation of territorially-based food identity and more recently experimented innovative forms of collective and public action to support transitions to sustainable territorial food systems. In Italy, the biodistrict frame has progressively been legitimized and recently adopted as a legal framework, while in France, despite many regional experiences focused on organic agriculture, the legal framework recently established with the Territorial Food System policy, officially driven by the agroecological transition paradigm, leaves a very variable place to organic agriculture and its principles, depending on local features and power configurations. Our objective in this paper is to understand these processes of institutionalisation. Based on a focused review of the French and Italian literature on this issue and on the analysis of the relative place of organics in policies, experiences and debates in France and Italy over the five last decades, we show that these processes of institutionalisation result from specific interplays between science, policy and experience, where the related actors take a different role, leading to different configurations and favouring different framings.